2020
DOI: 10.5588/ijtld.19.0106
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control in China and the road to Healthy China 2030

Abstract: Healthy China 2030 aims to reduce the adult smoking rate from 27.7% in 2015 to 20% by 2030. Achieving this goal requires a review of the tobacco control measures introduced in China to date, the gaps that remain and the opportunities ahead. In 2008, the World Health Organization introduced six measures to reduce demand for tobacco called MPOWER. The progress China has made in implementing these measure varies: 1) monitor tobacco use and prevention policies. The surveillance on tobacco use has been rigorous, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 0 publications
0
27
1
Order By: Relevance
“…In 2010, Chinese Center for Disease Control and Prevention carried out the Global Adult Tobacco Survey (GATS) in China and reported that smoking rate was 28.1% (52.9% of males and 2.4% of females) among Chinese adults [ 30 ]. The China Adult Tobacco Survey (CATS) in 2015 found the smoking rate was 27.7% among Chinese adults (52.1% of males and 2.7% of females), which did not change significantly from the results reported in 2010 [ 31 ]. In the current study, 75.7% included patients were female, which resulted in only 13.1% patients had a history of smoking.…”
Section: Discussionmentioning
confidence: 89%
“…In 2010, Chinese Center for Disease Control and Prevention carried out the Global Adult Tobacco Survey (GATS) in China and reported that smoking rate was 28.1% (52.9% of males and 2.4% of females) among Chinese adults [ 30 ]. The China Adult Tobacco Survey (CATS) in 2015 found the smoking rate was 27.7% among Chinese adults (52.1% of males and 2.7% of females), which did not change significantly from the results reported in 2010 [ 31 ]. In the current study, 75.7% included patients were female, which resulted in only 13.1% patients had a history of smoking.…”
Section: Discussionmentioning
confidence: 89%
“…A hopeful sign is that China has ratified the World Health Organization (WHO) Framework Convention on Tobacco Control since 2005, and the Chinese tobacco epidemic has been addressed by the Chinese government although it is the owner of the largest cigarette monopoly worldwide 43 . Additionally, the government's latest healthcare plan, Healthy China 2030, has set a goal to reduce the adult smoking rate to 20% by 2030 44 . The WHO introduced six measures for tobacco control in 2008, called MPOWER: monitor tobacco use and prevention policies; protect people from tobacco use; offer help to quit tobacco use; warn about the dangers of tobacco; enforce bans on tobacco advertising, promotion, and sponsorship; and raise taxes on tobacco.…”
Section: Smoking Behavior Parametersmentioning
confidence: 99%
“…The WHO introduced six measures for tobacco control in 2008, called MPOWER: monitor tobacco use and prevention policies; protect people from tobacco use; offer help to quit tobacco use; warn about the dangers of tobacco; enforce bans on tobacco advertising, promotion, and sponsorship; and raise taxes on tobacco. Many countries have made significant progress in implementing these measures, but China still has a long way to go 44 . Furthermore, with the development of computer networks, online tobacco marketing has become a serious obstacle for tobacco control because of high volumes and wide coverage in China 45 .…”
Section: Smoking Behavior Parametersmentioning
confidence: 99%
“…However, these countries are significantly different from other countries in terms of tobacco control and air pollution. Especially in China, contrary to the trend of decreasing number of smokers in the United States, the number of smokers in China has increased significantly (43)(44)(45). Therefore, in this field, Chinese research should pay full attention to the impact of smoking and other risk factors on COPD patients.…”
Section: Discussionmentioning
confidence: 99%